Meningkatkan Pemahaman Masyarakat Tentang Pentingnya Vaksinasi di Kampung Yanamaa Arso Pir 1 Kabupaten Keerom Papua - Rampa, Ester; Lantang, Daniel; Sinaga, Herlando; Romadhonni, Tika; Manugan, William; Prastyawati, Rini (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2022)
Vaccination is the process of administering vaccines by injection into the body or dripping into the mouth to increase the production of antibodies to ward off certain diseases. The implementation of this community service activity uses several methods, namely: the presentation method, this method was chosen to explain the importance of vaccination. Question and answer method, this method is very important to find out the insight of the people in Yanamaa Arso Pir 1 village, Keerom Regency regarding COVID-19 vaccination during the current pandemic. In addition, Sharing Session on COVID-19 vaccination was also carried out. Sharing session are given to the community in providing input and guidance for the material obtained. This activity will be held on November 19, 2021. The results of this service show that the people in Yanamaa Arso Pir 1 Village, Keerom Regency are very enthusiastic about participating in the activity from beginning to end.